Multifocal Osteonecrosis Secondary to Chronic Alcohol Ingestion - Kazu Matsumoto; Hiroyasu Ogawa; Haruhiko Akiyama (Case Reports in Orthopedics)
Multifocal osteonecrosis is a relatively rare disorder with an estimated incidence of around 3% among patients diagnosed as having osteonecrosis. Multifocal osteonecrosis is caused by the several conditions including corticosteroid treatment, coagulation disorders, connective tissue disorders including systemic lupus erythematosus (SLE), inflammatory bowel disease, renal transplantation, and underlying malignancies. Alcohol abuse is one of the risk factors for osteonecrosis, and alcohol-induced osteonecrosis is 5% among all the osteonecrosis. Furthermore, the overall incidence of alcohol-induced multifocal osteonecrosis was approximately 6% among all the osteonecrosis induced by the alcohol. Therefore, here, we report an extremely rare case of alcohol-induced multifocal osteonecrosis involving three joints (two knees and one hip) and review the related literature.